Influence of Angular Thrust in the Measurement of Torque in the SPT-T - Castro Piovan, Thiago Teixeira de [UNESP]; Palcheco Peixoto, Anna Silvia [UNESP]; Manzanal, D.; Sfriso, A. O. (Ios Press, 2015)
Skin friction of piles can be calculated with the torque measurement in the Standard Penetration Test, SPT-T, proposed by [1]. The purpose of this paper is to provide understating of the influence of angular thrust and rotational speed in this measure. It was used the database of [2] research studying three different site locations in Brazil containing simultaneous measurements of torque and its rotational speed. In addition, the elaboration of curves and statistical analysis made possible to have a better comprehension of the angular thrust behavior before and after the maximum torque is obtained as well as observe patterns and a predominant rotational speed for this test procedure.
Keywords: SPT-T; angular thrust; torque measurement; rotational speed